Determinants of smallholder farmers’ extent of participation in climate-smart agricultural projects in Kakamega County, Kenya - Janet Julie Okumu; Kenneth Waluse Sibiko; Phoebe Bwari Mose; Kevin Okoth Ouko (Cogent Social Sciences)
Climate-Smart Agriculture (CSA) presents the opportunity to meet the world increasing food demands in the face of climate variability. In Kenya, CSA has been promoted as a means of adapting to climate change among Kenyan farmers under Kenya Climate Smart Agriculture Project (KCSAP) and farmers’ participation is key. This study, therefore, sought to identify the extent of participation in climate-smart agricultural projects (CSAPs) in terms of longevity of farmers’ participation in CSAPs and the number of climate-smart agricultural practices adopted from the projects by the farmers in Kakamega County, Kenya. Multi-stage sampling technique was employed to collect cross-sectional primary data from 240 project participants in Kakamega County, Kenya. Data collected were analyzed using descriptive statistics and Tobit regression model. Results revealed that farmers’ extent of participation in CSAPs in terms of both longevity and number of climate-smart practices adopted from the project was positively and significantly influenced by the type of project funder and number of climate-smart practices offered by the projects. The longevity was significantly and negatively influenced by frequency of extension visits and distance to the market while the number of climate-smart practices adopted was significantly negatively influenced by distance to the market and legal land ownership status. The study recommended the need for expansion and promotion of climate-smart agricultural projects to non-benefiting communities in order to accelerate economic growth and poverty reduction through partnerships between the national and international governments funding agricultural projects and closer collaboration with local leaders, extension agents and more youthful farmers.